INVESTIGATION OF INCREASED LEVELS OF ANXIETY AND DEPRESSION IMPACT ON THE QUALITY OF LIFE IN PATIENTS WITH IRRITABLE BOWEL SYNDROME - Kucher, S.V.; Mudra, U.O.; Hanberher, I.I.; Mysula, M.S.; Mysula, Yu.I.; Dzhyvak, V.H.; Vastyanov, R.S. (World of Medicine and Biology, 2025)
The purpose of the study was to determine the effect of elevated levels of anxiety and depression on the quality of life of patients with irritable bowel syndrome depending on the frequency of exacerbations of the disease. The study included 72 patients aged 18 to 67 years with a clinically confirmed diagnosis of irritable bowel syndrome. Patients were stratified into three groups according to the frequency of exacerbations: rare (group A), moderate (group B) and frequent (group C). The study included an assessment of quality of life using the SF-36 questionnaire, depression level using the Beck Depression Inventory and anxiety level using the GAD-7 scale. The results showed a significant decrease in all quality of life indicators in patients with frequent exacerbations of irritable bowel syndrome, especially on the scales of physical functioning, vital activity, mental health, and social functioning. At the same time, a statistically significant increase in Beck Depression Inventory and GAD-7 scores was noted in these groups, indicating a high level of emotional distress. Correlation analysis confirmed a close inverse relationship between anxiety/depression indicators and quality of life scales. The results obtained emphasise the need for a biopsychosocial approach to the treatment of patients with irritable bowel syndrome with mandatory screening of emotional state and the use of psycho-emotional support as a supplement to gastroenterological therapy. The introduction of multidisciplinary support improves quality of life, reduces the frequency of relapses and increases the effectiveness of treatment.
Keywords: irritable bowel syndrome; quality of life; anxiety disorders; depression; SF-36; psychoemotional state